Polypropylene resin composition
By combining ultra-high molecular weight propylene homopolymer with organic materials and using a specific processing technology, a microporous membrane with good Gurley permeability and mechanical properties is prepared, which solves the problems of insufficient air transmission rate and mechanical properties in the existing technology and is suitable for applications such as filtration membranes and diaphragms.
Patent Information
- Application Number
- CN202380094433.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-21
- Filing Date
- 2023-10-02
- Publication Date
- 2025-10-14
AI Technical Summary
Existing microporous membrane materials have deficiencies in air transmission rate (Gurley permeability) and mechanical properties, making it difficult to meet the needs of certain applications.
A microporous membrane with good Gurley permeability and mechanical properties is prepared by combining ultra-high molecular weight propylene homopolymer and organic materials to form a microporous membrane through specific proportions and processing techniques, including biaxial orientation and volatile solvent extraction.
The high air transmission rate and excellent mechanical properties of the microporous membrane are achieved, making it suitable for various applications such as filtration membranes and separators, especially battery separators.
Smart Images

Figure BDA0005554544010000031 
Figure BDA0005554544010000032 
Figure BDA0005554544010000061
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to a polypropylene resin composition comprising an ultra-high molecular weight propylene homopolymer, which is used to form a microporous film having good Gurley permeability (measured according to ISO 5636) and good mechanical properties. BACKGROUND
[0002] Microporous films made of polymeric materials are used in various applications, for example, filtration and separation membranes for medical and industrial uses, and separators such as battery separators and capacitor separators. In particular, with the recent growing demand for secondary batteries as power sources for mobile phones, mobile personal computers and automobiles, the demand for battery separators is also growing.
[0003] EP 1 464 669 relates to microporous films made essentially of high molecular weight polyethylene or a blend of polyethylene and polypropylene. However, its air transmission rate (Gurley permeability) can be improved. SUMMARY
[0004] The present disclosure relates to a polypropylene resin composition comprising:
[0005] A) from 10 wt% to 70 wt% of an ultra-high molecular weight propylene homopolymer, optionally containing up to 1.0 wt% of ethylene derived units, characterized in that:
[0006] - two melting points are present in the DSC thermogram measured according to ISO 11357-3 with a heating and cooling rate of 20°C / min;
[0007] - the higher melting point ranges from 155°C to 170°C measured according to ISO 11357-3 with a heating and cooling rate of 20°C / min;
[0008] - the fraction soluble in xylene at 25°C is comprised between 6.0 wt% and 2.0 wt% measured according to ISO 16 152 - 2005;
[0009] - the isotactic pentad mmmm% measured by NMR as reported in the Examples section ranges from 96.5 mol% to 90.0 mol%; 13 NMR measured isotactic pentad mmmm% ranges from 96.5 mol% to 90.0 mol%;
[0010] - the intrinsic viscosity (IV) measured in tetrahydronaphthalene at 135°C ranges from 5.5 dl / g to 12.0 dl / g;
[0011] - the fraction soluble in xylene at 25°C is comprised between 6.0 wt% and 2.0 wt% measured according to ISO 16 152 - 2005;2 measured at an acceleration of 0.070 N;
[0012] B) 30 to 90 wt.-% of an organic material selected from the group consisting of: organic acid esters; adipic acid esters, glyceric acid esters; phosphoric acid esters; paraffins; waxes; and mineral oils.
[0013] wherein the sum of the amount of component A) and the amount of component B) in wt.-% amounts to 100 wt.-%. DETAILED DESCRIPTION
[0014] The present disclosure relates to a polypropylene resin composition comprising:
[0015] A) 10 to 70 wt.-%; preferably 20 to 60 wt.-%; more preferably 30 to 57 wt.-% of an ultra-high molecular weight propylene homopolymer, which optionally contains up to 1.0 wt.-%, preferably up to 0.6 wt.-% of ethylene derived units, characterized in that:
[0016] - two melting points are present in the DSC thermogram measured according to ISO 11357-3 with a heating and cooling rate of 20 °C / min; preferably the lower melting point ranges from 135 °C to 150 °C;
[0017] - the higher melting point ranges from 155 °C to 170 °C; preferably from 157 °C to 168 °C, measured according to ISO 11357-3 with a heating and cooling rate of 20 °C / min;
[0018] - the fraction soluble in xylene at 25 °C measured according to ISO 16 152 - 2005 is comprised between 6.0 wt.-% and 2.0 wt.-%; preferably between 5.0 wt.-% and 2.5 wt.-%; more preferably between 4.0 wt.-% and 2.8 wt.-%;
[0019] - the isotactic pentad mmmm% measured by NMR as reported in the examples section ranges from 96.5 mol-% to 90.0 mol-%; preferably from 96.0 mol-% to 93.0 mol-%; more preferably from 95.5 mol-% to 93.5 mol-%; 13 NMR measured isotactic pentad mmmm% ranges from 96.5 mol-% to 90.0 mol-%; preferably from 96.0 mol-% to 93.0 mol-%; more preferably from 95.5 mol-% to 93.5 mol-%;
[0020] - the intrinsic viscosity (IV) measured in tetrahydronaphthalene at 135 °C ranges from 5.5 dl / g to 12.0 dl / g; preferably from 7.0 dl / g to 11.0 dl / g; more preferably from 8.0 dl / g to 10.0 dl / g;
[0021] - a melt strength higher than 0.070 N; preferably higher than 0.080 N; more preferably higher than 0.090 N, measured according to ISO 16790-2005 at 250°C and with an acceleration equal to 6 mm / s 2 - a melt strength higher than 0.070 N; preferably higher than 0.080 N; more preferably higher than 0.090 N, measured according to ISO 16790-2005 at 250°C and with an acceleration equal to 6 mm / s
[0022] B) from 30 to 90 wt.%; preferably from 40 to 80 wt.%; more preferably from 43 to 70 wt.% of an organic material selected from: organic acid esters (such as dioctyl phthalate,
[0023] dioctyl phthalate, diheptyl phthalate and dibutyl phthalate), adipates, glycerol esters; phosphates (such as trioctyl phosphate); paraffins (such as liquid paraffin and solid paraffin); waxes; and mineral oils;
[0024] wherein the sum of the amount of component A) and the amount of component B) (in wt.%) is equal to 100 wt.%.
[0025] Preferably, the organic material component B) is selected from liquid paraffin, solid paraffin; waxes; and mineral oils; more preferably, the organic material component B) is a mineral oil; even more preferably, the organic material component B) is white mineral oil (CAS 8042-47-5).
[0026] Preferably, the propylene homopolymer of the present disclosure is not nucleated.
[0027] Preferably, the homopolymer of the present disclosure shows a melt strength value lower than 0.30 N.
[0028] Preferably, the homopolymer of the present disclosure shows a polydispersity index PI comprised between 4.5 and 7.5; more preferably between 5.0 and 7.2; more preferably between 5.5 and 6.5, measured according to ISO 6721-10.
[0029] Preferably, the homopolymer of the present disclosure shows a tensile modulus ranging from 2100 MPa to 1100 MPa; preferably from 1800 MPa to 1200 Mpa.
[0030] Preferably, the homopolymer of the present disclosure shows a Charpy impact test ranging from 4.0 kJ / m2 to 11.0 kJ / m2; preferably from 5.5 kJ / m2 to 9.0 kJ / m2 at 23°C.
[0031] The propylene homopolymers disclosed herein can be prepared by a process comprising polymerizing propylene, optionally with ethylene, in the presence of a Ziegler-Natta catalyst. An essential component of the catalyst is a solid catalyst component comprising a titanium compound having at least one titanium-halogen bond and an electron donor compound, both supported on a magnesium halide in active form. Another essential component (cocatalyst) is an organoaluminum compound, such as an alkylaluminum compound. An external donor is optionally added.
[0032] Catalysts having the above characteristics are known in the patent literature; particularly advantageous are the catalysts described in U.S. Patent 4,399,054 and European Patent 45977. Other examples can be found in U.S. Patent 4,472,524.
[0033] The solid catalyst component used in the catalyst comprises, as electron donor (internal donor), a compound selected from the group consisting of ethers, ketones, lactones, compounds containing N, P and / or S atoms, and esters of mono- and di-carboxylic acids.
[0034] Particularly suitable electron donor compounds are esters of succinic acid (succinates). Preferably, the succinates present in the solid catalyst component are selected from succinates of formula (I)
[0035]
[0036] wherein the groups R1and R2, equal to or different from each other, are C1-C 20 linear or branched alkyl, alkenyl, cycloalkyl, aryl, aralkyl or alkaryl, optionally containing heteroatoms; and the groups R3and R4, equal to or different from each other, are C1-C 20 alkyl, C3-C20 cycloalkyl, C5-C20 aryl, aralkyl or alkaryl, provided that at least one of them is a branched alkyl; said compound being a (S,R) or (R,S) type stereoisomer with respect to the two asymmetric carbon atoms identified in the structure of formula (I).
[0037] R1and R2are preferably C1-C8 alkyl, cycloalkyl, aryl, aralkyl and alkaryl. Particularly preferred are compounds in which R1and R2are selected from primary alkyl groups, in particular branched primary alkyl groups. Examples of suitable R1and R2groups are methyl, ethyl, n-propyl, n-butyl, isobutyl, neopentyl, 2-ethylhexyl. Particularly preferred are ethyl, isobutyl and neopentyl.
[0038] Particularly preferred are compounds in which the R3and / or R4groups are secondary alkyl groups such as isopropyl, sec-butyl, 2-pentyl, 3-pentyl or cycloalkyl groups such as cyclohexyl, cyclopentyl, cyclohexylmethyl.
[0039] Examples of the above compounds are 2,3-bis(trimethylsilyl)succinic acid diethyl ester, 2,3-bis(2-ethylbutyl)succinic acid diethyl ester, 2,3-dibenzylsuccinic acid diethyl ester, 2,3-diisopropylsuccinic acid diethyl ester, 2,3-diisopropylsuccinic acid diisobutyl ester, 2,3-bis(cyclohexylmethyl)succinic acid diethyl ester, 2,3-diisobutylsuccinic acid diethyl ester, 2,3-dineopentylsuccinic acid diethyl ester, 2,3-dicyclopentylsuccinic acid diethyl ester, 2,3-dicyclohexylsuccinic acid diethyl ester, in (S,R) (S,R) pure form or in mixture form, optionally in racemic form.
[0040] Particularly suitable electron donor compounds are esters of phthalic acid and 1,3-diethers of the formula
[0041]
[0042] wherein R I and R II are identical or different and are a C1-C 18 alkyl radical, a C3-C 18 cycloalkyl radical or a C7-C 18 aryl radical; R III and R IV are identical or different and are a C1-C4 alkyl radical; or are 1,3-diethers, wherein the carbon atom in position 2 belongs to a cyclic or polycyclic structure consisting of 5, 6 or 7 carbon atoms or 5-n or 6-n' carbon atoms and n nitrogen atoms and n' heteroatoms selected from the group consisting of N, O, S and Si, respectively, wherein n is 1 or 2 and n' is 1, 2 or 3, which structure contains two or three unsaturations (cyclopolyene structure) and is optionally condensed with other cyclic structures, or is substituted by one or more substituents selected from the group consisting of straight-chain or branched alkyl radicals, cycloalkyl radicals, aryl radicals, aralkyl radicals, alkylaryl radicals and halogens, or is condensed with other cyclic structures and is substituted by one or more of the above-mentioned substituents, one or more of the above-mentioned alkyl radicals, cycloalkyl radicals, aryl radicals, aralkyl radicals or alkylaryl radicals and optionally condensed cyclic structures containing one or more heteroatoms as substituents for carbon atoms or hydrogen atoms or both.
[0043] Ethers of this type are described in published European patent applications 361493 and 728769.
[0044] Representative examples of the diethers are 2-methyl-2-isopropyl-1,3-dimethoxypropane, 2,2-diisobutyl-1,3-dimethoxypropane, 2-isopropyl-2-cyclopentyl-1,3-dimethoxypropane, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, 9,9-bis(methoxymethyl)fluorene.
[0045] Other suitable electron donor compounds are phthalic esters such as diisobutyl phthalate, dioctyl phthalate, diphenyl phthalate and benzyl butyl phthalate.
[0046] The preparation of the above catalyst components is performed according to various methods.
[0047] For example, MgCl2.nROH adducts, in particular in the form of spherical particles, where n is generally from 1 to 3 and ROH is ethanol, butanol or isobutanol, are reacted with an excess of TiCl4containing the electron donor compound. The reaction temperature is generally from 80°C to 120°C. The solid is then separated and re-reacted once more with TiCl4in the presence or absence of the electron donor compound, after which it is separated and washed with aliquots of hydrocarbons until all the chloride ions have disappeared.
[0048] In the solid catalyst component, the titanium compound, indicated as Ti, is generally present in an amount of from 0.5% to 10% by weight. The amount of electron donor compound, with respect to the magnesium dihalide, which remains fixed on the solid catalyst component is generally from 5 to 20 moles %.
[0049] The titanium compounds which can be used for the preparation of the solid catalyst component are halides and halogeno-alcohols of titanium. Titanium tetrachloride is the preferred compound.
[0050] The above reaction forms the active form of the magnesium halide. Other reactions are known in the literature which form the active form of the magnesium halide starting from magnesium compounds other than halides, such as magnesium carboxylates.
[0051] The alkyl aluminium compounds used as co-catalysts include trialkylaluminium such as triethylaluminium, triisobutylaluminium, tri-n-butylaluminium, and linear or cyclic alkyl aluminium compounds containing two or more Al atoms bonded to each other through O or N atoms or SO4 or SO3 groups.
[0052] The Al-alkyl compounds are generally used in such an amount that the Al / Ti ratio is from 1 to 1000.
[0053] The electron donor compounds which can be used as external donors include aromatic acid esters such as alkyl benzoates, and in particular silicon compounds containing at least one Si-OR bond, where R is a hydrocarbon radical.
[0054] Examples of silicon compounds are (tert-butyl)2Si(OCH3)2, (cyclohexyl)(methyl)Si(OCH3)2, (cyclopentyl)2Si(OCH3)2and (phenyl)2Si(OCH3)2and (1,1,2-trimethylpropyl)Si(OCH3)3.
[0055] 1,3-Diethers of the above-mentioned formula can also be used advantageously. If the internal donor is one of these diethers, the external donor can be omitted.
[0056] In particular, component A) is preferably prepared by using a catalyst containing a phthalate as internal donor and (cyclopentyl)2Si(OCH3)2 as external donor, or the 1,3-diether as internal donor, even if many other combinations of the aforementioned catalyst components may allow the composition according to the invention to be obtained.
[0057] The polymerization is typically carried out at a temperature of 20°C to 120°C, preferably 40°C to 80°C. When the polymerization is carried out in the gas phase, the operating pressure is typically between 0.5 MPa and 5 MPa, preferably between 1 MPa and 4 MPa. In bulk polymerization, the operating pressure is typically between 1 MPa and 8 MPa, preferably between 1.5 MPa and 5 MPa. Hydrogen is typically used as a molecular weight regulator. The polymerization can be carried out in the gas phase, in a slurry, or in a solution. In one or more reactors, the polymerization is preferably carried out in two slurry reactors operated in series.
[0058] The composition of the present disclosure can be obtained by a method comprising the steps of mixing component A) and component B) to perform granulation in a mixer.
[0059] The compositions of the present disclosure can be used to form microporous membranes having good Gurley permeability and good mechanical properties.
[0060] The process most suitable for obtaining the microporous membrane according to the present disclosure comprises the steps of mixing the organic material component B) with component A), heating and melting the mixture, extruding the melt into a sheet, simultaneously or sequentially biaxially orienting the sheet, and then extracting the liquid with a volatile solvent (e.g., dichloromethane).
[0061] Optionally, the film can be heat-set. This final step enhances dimensional stability and prevents shrinkage or wrinkling when heated, which is important for safety and control of final performance.
[0062] The microporous membranes obtained using the compositions of the present disclosure show good Gurley permeability (measured according to ISO 5636).
[0063] Furthermore, the porosity measured according to the method described in the Examples is particularly good, preferably ranging from 30.0% to 60.0%, more preferably from 33.0% to 51.0%, and even more preferably from 34.0% to 45.0%.
[0064] The range of puncture resistance for a 20 pm standardized microporous membrane is from 700 g / 20 pm to 1200 g / 20 pm; preferably from 750 g / 20 pm to 1050 g / 20 pm; more preferably from 800 g / 20 pm to 998 g / 20 pm.
[0065] Another object of the present disclosure is the use of an ultra-high molecular weight propylene homopolymer component A) containing at most 1.0 wt% ethylene derived units for the production of a microporous membrane.
[0066] Another object of the present disclosure is a microporous membrane, preferably obtained using the above described process, having a Gurley permeability, measured according to ISO 5636, normalized to a thickness of 20 pm, lower than 1400 s / 100 ml 720 pm, preferably lower than 1300 s / 100 m / 20 pm.
[0067] Another object of the present disclosure is a microporous membrane, obtained using the above described process.
[0068] The following examples are given for the purpose of illustration and not limitation of the present disclosure.
[0069] Examples
[0070] Characterization
[0071] Xylene insoluble fraction
[0072] The xylene soluble fraction has been measured according to ISO 16 152-2005; in case of a solution volume of 250 ml, precipitation at 25°C for 20 minutes, with 10 minutes of solution agitation (magnetic stirrer), and drying at 70°.
[0073] Melt flow rate (MFR)
[0074] Measured according to ISO 1133 at 230°C and with a load of 21.6 kg, unless otherwise indicated.
[0075] Polydispersity (PI)
[0076] Dynamic testing of few grams of molten homopolymer was performed in rate sweep with a parallel plate rheometer at a temperature of 200°C according to ISO 6721-10. G' (storage modulus) and G" (loss modulus) were measured as a function of frequency. From the rate sweep data, PI is defined by PI = 105 / Gc, where Gc is the cross-over modulus as the modulus value at G' = G".
[0077] Melting temperature via differential scanning calorimetry (DSC)
[0078] The melting point (Tm) of the polymers was measured by differential scanning calorimetry (DSC) on a Perkin Elmer DSC-1 calorimeter previously calibrated against the melting point of indium according to ISO 11357-1, 2009 and 11357-3, 2011 at 20 °C / min. The weight of the sample in each DSC crucible was kept at 6.0 ± 0.5 mg.
[0079] To obtain the melting point, the weighed sample was sealed into an aluminum pan and heated to 200 °C at 20 °C / min. The sample was kept at 200 °C for 2 minutes to allow complete melting of all crystallites, then cooled to 5 °C at 20 °C / min. After 2 minutes of standing at 5 °C, the sample was heated to 200 °C at 20 °C / min for a second run time. In this second heating run, the peak temperature (Tp,m) was taken as the melting temperature.
[0080] Homopolymer and propylene / ethylene copolymer 13 C NMR
[0081] 13 C NMR spectra were acquired on a Bruker AV-600 spectrometer equipped with a cryogenically cooled probe, operating in Fourier transform mode at 120 °C at 160.91 MHz.
[0082] S at 29.9 ppm ββ The peak of carbon at 29.9 ppm (nomenclature according to "Monomer sequence distribution in ethylene-propylene rubbers measured by 13C NMR. 3. Use of reaction probability models" C. J. Carman, R. A. Harrington and C. E. Wilkes, Macromolecules, 1977, 10, 536) was used as internal reference. The samples were dissolved in 1,1,2,2-tetrachloroethane-d2 at 8 wt / v% concentration at 120 °C. Each spectrum was acquired with 90° pulses, with a 15 seconds delay between pulse and CPD to remove 1H-13C coupling. 512 transients were stored in 32K data points using a spectral window of 9000 Hz.
[0083] The spectral distribution, the triplet distribution, the evaluation of the composition are made according to Kakugo ("Carbon-13 NMR determination of monomer sequence distribution in ethylene-propylene copolymers prepared with δ-titanium trichloride-diethylaluminum chloride" M. Kakugo, Y. Naito, K. Mizunuma and T. Miyatake, Macromolecules, 1982, 15, 1150) using the following equations:
[0084] PPP = 100 T ββ / S PPE = 100 T βδ / S EPE = 100 T δδ / S
[0085] PEP = 100 S ββ / S PEE = 100 S βδ / S EEE = 100 (0.25 S γδ + 0.5 S δδ ) / S
[0086] S = T ββ + T βδ + T δδ + S ββ + S βδ + 0.25 S γδ + 0.5 S δδ
[0087] The molar percentage of ethylene content is evaluated using the following equation:
[0088] The weight percentage of ethylene content is evaluated using the following equation:
[0089]
[0090] where P mol% is the molar percentage of propylene content, and MW E and MW P are the molecular weight of ethylene and propylene, respectively.
[0091] The product of the reactivity ratios r1r2 is calculated according to Carman (C.J. Carman, R.A. Harrington and C.E. Wilkes, Macromolecules, 1977; 10, 536) as:
[0092]
[0093] The tacticity of the propylene sequences is calculated as mm content from the ratio of PPP mmT ββ (28.90 ppm to 29.65 ppm) to total T ββ (29.80 ppm to 28.37 ppm).
[0094] Intrinsic viscosity
[0095] The sample is dissolved at 135°C by means of tetraline and then poured into the capillary viscometer. The viscometer tube (Ubbelohde type) is surrounded by a cylindrical glass jacket; this arrangement allows temperature control with a circulating thermostatted liquid. The descent of the meniscus is timed by means of a photoelectric device. The passage of the meniscus in front of the upper lamp starts a counter with a quartz crystal oscillator. When it passes through the lower lamp, the meniscus stops the counter and the efflux time is recorded: this is converted into intrinsic viscosity values by means of the Huggins equation, provided that the flow time of the pure solvent is known under the same experimental conditions (same viscometer and same temperature). A single polymer solution is used to determine the IV.
[0096] Melt strength
[0097] The melt strength is measured according to ISO 16790-2005 by means of a Haul-off Melt Strength Meter produced by Geottfert Werkstoff Pruefmaschinen, Germany. This system measures the extensional properties of a polymer melt by pulling a vertical melt strand at a constant pull-off speed or at a linear or exponential accelerated speed. The HAUL-OFF system measures the force required to elongate the strand and calculates the elongation stress, the draw ratio, the apparent elongation and the viscosity. The polymer is melted and plasticized by means of a capillary rheometer and then extruded from a die with a diameter of 1 mm, a length of 30 mm and an entrance angle of 180°. The test is performed at 250°C. The distance from the capillary exit to the center of the sensor pulley is 150 mm. In each temperature test, the acceleration equal to 6 mm / s 2 is applied to stretch the filament and its elongation is measured by means of an angular sensor. In addition to the entire curve, the draw ratio (dimensionless value) and the force (cN) values are recorded as final results. The value of the melt strength is the maximum force value of the curve.
[0098] Charpy impact test
[0099] Charpy impact test measured on compression samples according to ISO 179-1 eA and ISO 1873-2
[0100] Tensile modulus
[0101] Tensile modulus measured on compression samples according to ISO 527-2 and ISO 1873-2
[0102] Porosity
[0103] Porosity was measured by measuring the mass and thickness of a 5 cm x 5 cm film sample and calculating the free volume related to the standard density given in the following equation.
[0104]
[0105] In the equation, m is the mass of the sample, p is the density of the substrate (0.915 g / cm 3 ), A is the area of the sample, and d is the measured thickness.
[0106] Puncture resistance and deformation:
[0107] Determined on microporous films according to ASTM D 4833 method. Punch diameter 8 mm, crosshead speed: 300 mm / min. Puncture resistance has been normalized on 20 pm films.
[0108] Example 1 - Preparation of a homopolymer
[0109] Procedure for preparing the solid catalyst component
[0110] The solid catalyst used in the following examples was prepared according to example 10 of international patent application WO 00 / 63261. Triethylaluminium (TEAL) was used as co-catalyst and dicyclopentyl dimethoxysilane as external donor, the weight ratios are indicated in table 1.
[0111] Polymerization
[0112] The polymerization run in a series of two reactors equipped with means for transferring the product from one reactor to the one next to it in continuous mode. The two reactors are liquid phase loop reactors. Propylene is the main solvent, hydrogen is used as molecular weight regulator. The gas phase is continuously analyzed via gas chromatography.
[0113] At the end of the run, the powder was discharged and dried under nitrogen flow. The main polymerization conditions and polymer properties are reported in table 1 and table 2.
[0114] Table 1 - Polymerization conditions
[0115] Example 1 TEAL / catalyst (wt ratio) 4.3 TEAL / external donor (wt ratio) 3 First loop Temperature °C 75 Pressure barg 40 [H2 ppmol] <10 pp mol Separation wt% 50 Second loop Temperature °C 75 Pressure barg 40 [H2 ppmol] <10 pp mol Separation wt% 50
[0116] The characteristics of the polymer of Example 1 are reported in Table 2.
[0117] Table 2
[0118]
[0119]
[0120] The polymer of Example 1 (component A) was mixed with white mineral oil sold by Kukdong (CAS 8042-47-5) (component B).
[0121] The obtained composition was melt formed into a sheet, the resulting sheet was stretched 7x7 times in biaxial direction. The sheet was then treated with dichloromethane to remove component B). The characteristics of the obtained microporous membrane are reported in Table 3.
[0122] Table 3
[0123]
[0124] * Normalized for 20 pm sheet
[0125] Gurley permeability was measured according to ISO 5636, the value has been normalized for 20 pm sheet.
Claims
1. A polypropylene resin composition, comprising: A) 10 to 70 wt% of an ultra-high molecular weight propylene homopolymer, optionally containing up to 1.0 wt% of ethylene-derived units characterized by: - two melting points in the DSC thermogram measured according to ISO 11357-3 with a heating and cooling rate of 20°C / min; - the higher melting point is in the range of 155°C to 170°C, measured according to ISO 11357-3 at a heating and cooling rate of 20°C / min; - the fraction soluble in xylene at 25° C., measured according to ISO 161522005, is comprised between 6.0% and 2.0% by weight; - as reported in the Examples section of the description, with C 13 The isotactic pentad mmmm% measured by NMR ranged from 96.5 mol% to 90.0 mol%; - an intrinsic viscosity (IV) measured in tetralin at 135° C. ranging from 5.5 dl / g to 12.0 dl / g; - According to ISO 16790-2005 at 250°C and applied at 6 mm / s 2 The melt strength measured under the acceleration is higher than 0.070N; B) 30% to 90% by weight of an organic material selected from the group consisting of: organic acid esters; adipates, glycerides; phosphates; paraffins; waxes; and mineral oils.
2. The polypropylene resin composition according to claim 1, wherein in component A): there are two melting points in a DSC thermogram measured according to ISO 11357-3 at a heating and cooling rate of 20°C / min; and the lower melting point is in the range of 135°C to 150°C.
3. The polypropylene resin composition according to claim 1 or 2, wherein in component A): the higher melting point measured at a heating and cooling rate of 20°C / min according to ISO 11357-3 ranges from 157°C to 168°C.
4. The polypropylene resin composition according to any one of claims 1 to 3, wherein in component A): the fraction soluble in xylene at 25°C measured according to ISO 16 152-2005 is comprised between 5.0 wt% and 2.5 wt%.
5. The polypropylene resin composition according to any one of claims 1 to 4, wherein in component A): the fraction soluble in xylene at 25°C measured according to ISO 16 152-2005 is comprised between 4.0 wt% and 2.8 wt%.
6. The polypropylene resin composition according to any one of claims 1 to 5, wherein in component A): C 13 The isotactic pentad mmmm% measured by NMR ranged from 96.0 mol% to 93.0 mol%.
7. The polypropylene resin composition according to any one of claims 1 to 6, wherein component A) ranges from 20 wt% to 60 wt%, and component B) ranges from 40 wt% to 80 wt%.
8. The polypropylene resin composition according to any one of claims 1 to 7, wherein component B) is selected from the group consisting of liquid paraffin, solid paraffin; wax; and mineral oil.
9. The polypropylene resin composition according to any one of claims 1 to 8, wherein component B) is mineral oil.
10. The polypropylene resin composition according to any one of claims 1 to 9, wherein in component A): 2 The melt strength measured under the acceleration condition is higher than 0.080N.
11. The polypropylene resin composition according to any one of claims 1 to 10, wherein in component A): the intrinsic viscosity (IV) measured in tetralin at 135°C is in the range of 7.0 dl / g to 11.0 dl / g.
12. The polypropylene resin composition according to any one of claims 1 to 11, wherein component A) ranges from 30 wt% to 57 wt%, and component B) ranges from 43 wt% to 70 wt%.
13. A method for obtaining a microporous membrane according to any one of claims 1 to 12, comprising the following steps: The organic material component B) is mixed with component A), the mixture is heated and melted, the melt is extruded into a sheet, the sheet is biaxially oriented simultaneously or sequentially, and the liquid is then extracted with a volatile solvent.
14. The method of claim 13, wherein the volatile solvent is dichloromethane.
15. Use of the ultra-high molecular weight propylene homopolymer containing up to 1.0 wt% ethylene according to claims 1 to 12 for producing microporous membranes.
Citation Information
Patent Citations
Components and catalysts for the polymerization of olefins
EP0045977A2
Catalyst components and catalysts for the polymerization of alpha-olefins
US4399054A
Components and catalysts for the polymerization of olefins
US4472524A
Components and catalysts for the polymerization of olefins
WO2000063261A1